2023
DOI: 10.1039/d3fb00108c
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of different particle sizes of added olive leaves for the content of target polyphenols in virgin olive oil

Fereshteh Safarzadeh Markhali,
José A. Teixeira

Abstract: This figure highlights the most important findings of this study. The addition of dry ground olive leaves with 0.3 mm particle size prior to a short malaxation, significantly proved useful for increasing polyphenolic content and antioxidant capacity of the resulting virgin olive oil.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…The separations of the target polyphenols were performed using a reverse-phase Aquity UPLC BEH C18 column (100 mm × 2.1 mm i.d., 1.7 μm particle size, Waters Corporation) based on the gradient elution method described previously 14 with slight modifications. 15 The flow rate was 0.3 mL min −1 . The injection volume was 5 μL.…”
Section: Methodsmentioning
confidence: 99%
“…The separations of the target polyphenols were performed using a reverse-phase Aquity UPLC BEH C18 column (100 mm × 2.1 mm i.d., 1.7 μm particle size, Waters Corporation) based on the gradient elution method described previously 14 with slight modifications. 15 The flow rate was 0.3 mL min −1 . The injection volume was 5 μL.…”
Section: Methodsmentioning
confidence: 99%
“…A reverse-phase Aquity UPLC BEH C-18 column (100 mm × 2.1 mm, with 1.7 mm particle size, from Waters Corporation) was applied for the separation of analytes within the gradient elution program detailed previously. 13,14 The temperature remained constant at 45 °C. Eluent A (water/formic acid, 99.9/0.1 v/v) and eluent B (acetonitrile) were used as mobile phases at a ow rate of 0.3 mL min −1 .…”
Section: Hplc Analysesdetermination Of the Recovery Of Principal Poly...mentioning
confidence: 99%
“…Therefore, the production of olive oils with an increased content of phenolic compounds, which can additionally protect the oil from oxidation, is of great importance for the quality and oxidative stability of the product [ 22 ]. Until now, many attempts have been made to increase the content of phenolic compounds in olive oil, especially by optimizing the oil extraction conditions, such as the temperature and time of the malaxation of the olive paste [ 23 , 24 ], and, in more recently time, by the addition of natural sources of phenolic compounds, such as by-products from the olive and olive oil production, especially by olive leaf addition [ 25 , 26 , 27 ]. Although during the production of olive oils a small part of the leaves remains after the cleaning process, it should be emphasized that the intentional addition of a larger quantity of leaves would not be in accordance with EU regulations for virgin olive oils [ 28 ] since virgin olive oils are oils produced exclusively from olive fruits without any other additives.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the previous studies have been focused on the influence of the addition of leaves on the phenolic compounds and antioxidant activity of the oils but with contradictory results. Some studies reported an increase in the concentration of total phenols and antioxidant activity [ 25 , 27 , 29 , 30 , 33 ], while some reported a decrease or no changes in the content of phenolic compounds [ 32 , 34 , 35 ] after the addition of leaves. The results obtained in the research conducted on a laboratory scale are not always the same as those conducted on an industrial scale, even though the same malaxation times and temperatures of olive paste are used [ 36 ].…”
Section: Introductionmentioning
confidence: 99%